Primary cilia in osteoblasts and osteocytes are required for skeletal development and mechano-adaptation - Mariana Moraes de Lima Perini; Alyssa F. Fayemi; Julie N. Pugh; Elizabeth M. Scott; Karan Bhula; Austin Chirgwin; Olivia N. White; Nicolas F. Berbari; Jiliang Li (PLoS ONE, 2026)
Primary cilia play a crucial role in the development and mechanosensation of various tissue types, including bone. In this study, we investigated their role in bone growth and adaptation by targeting two cilia specific genes, IFT88 and MKS5. Conditional knockout (cKO) of IFT88 in osteoblasts significantly reduced body weight and femur length in mice compared to the littermate controls. Additionally, female IFT88 cKO mice exhibited a significant suppression of bone formation rate compared to the littermate controls. To further explore the role of primary cilia in osteocytes, osteocytes specific MKS5 cKO mice underwent axial ulnar loading at a peak force of 2.9N for females and 3.2N for males with 120 cycles per day for three consecutive days. Load induced bone formation rate was significantly decreased by 48% in males and 42% in females compared to the littermate control mice. These findings underscore the critical role of primary cilia in bone development and mechano-adaptation. They suggest that functional primary cilia in osteoblasts are essential for skeletal development, while those in osteocytes mediates mechanically induced bone formation, highlighting its potential as therapeutic targets for bone loss prevention.